Ultrasonography in lung pathologies: new perspectives - Demi, Libertario; Demi, Marcello; Smargiassi, Andrea; Inchingolo, Riccardo; Faita, Francesco; Soldati, Gino (Multidisciplinary respiratory medicine, 2014)
Background Nowadays, ultrasound techniques have not gained importance in the diagnosis and monitoring of lung pathologies yet because of the high mismatch in acoustic impedance between air and intercostal tissues. However, it is evident that B-mode imaging provides important information on pulmonary tissue, although in the form of image artifacts. Findings Notwithstanding medical evidences, there exists no ultrasound-based method dedicated to the lung, hampering de facto the full exploitation of ultrasound potentials. A chance is given by the experience acquired in other fields, where acoustic attenuation is used to estimate concentrations of suspended particles in liquids and of air-bubbles in aerated foods. Conclusions Custom hardware must be developed since commercial echographic equipment has been optimized to work with low acoustic impedance mismatches, and, in general, does not provide the primitive radiofrequency (RF) signals nor the possibility to tune key acquisition parameters such as ultrasound carrier frequency and pulse bandwidth, which are surely needed for our application.